The energy distribution of electrode in hollow cathode centered negative pressure arc. (October 2016) - Jiang, Fan; Yan, Zhaoyang; Chen, Shujun; Lu, Zhenyang
Abstract: As a new type of welding heat source, hollow cathode centered negative pressure arc (HCCNPA) has evenly distributed energy density in the center of the arc and a higher energy gradient at the boundary in comparison with traditional gas tungsten arc (GTA). With these changes, the brightness of the cathode increased significantly, which is the effect of inner arc plasma on the hollow cathode. To better understand of this, in present study the measurements of energy distribution between anode and cathode in HCCNPA were performed respectively by calorimetric calculation. Experiments were conducted to evaluate the influence of welding parameters on heat distribution of HCCNPA, and the results were compared with conventional GTAW process. It was found that the application of negative pressure in the hollow cathode greatly modified the energy distribution between anode and cathode. Though the energy demand of maintaining a stable arc increased with the application of negative pressure which reflected as the increase of arc voltage, the total energy used to electrode became lower. In particular, the energy in cathode increased and that in anode decreased as the negative pressure applied, and these differences increase as the current and arc length increase. Otherwise, the application of negative pressure in the hollow made the result arc constrained, so the HCCNPA has a more evenly distributed energy density in the center and a higher energy gradient at the boundary in comparison with the conventional GTA, which would enable the development of high quality applications.